Characterization of feeding in Chilean babies with cleft palate between 0 and 6 months - González Jara, Matías; Norambuena Norambuena, Scarlette; Inostroza Allende, Felipe; Lennon Zaninovic, Loreto; Quezada Gaponov, Camilo (Revista de Investigación en Logopedia, 2021)
Babies with cleft palate manifest problems in sucking dynamics, due to the communication between the nasal and oral cavity. The aim of the study was to characterize and compare general and feeding history in babies between 0 and 6 months old with post-foraminal clefts (PFC) and trans-foraminal clefts (TFC). Electronic records of care of 36 babies with PFC and TFC from a public hospital in Chile were reviewed. The data obtained between the PFC and TFC clefts types were compared using the R statistical software. Days of direct breastfeeding averaged 13.5 days in infants with PFC and 16.6 days in infants with TFC. Malnutrition occurs in 72.7% of babies with FPF and 40% of babies with TFC. Milk formula and bottle use were observed in more than 96% of the participants. The extraction of breast milk reached 25.2 days in PFC and 48.1 days in TFC. The indication of breast milk extraction methods, type of formula and type of utensil for feeding was mostly provided by a professional. It is believed that the time of direct breastfeeding was shorter than other national and international centers. The most used utensil was the bottle and the instructions for feeding were given mostly by professionals. It is concluded that there are no significant differences when comparing the feeding between both types of clefts.